(untitled) (Management and Connections Journal, 2024)
This research aims at verifying whether mayors’ and councilors’ Human Capital has influence on the fiscal performance of Brazilian municipalities. The existing literature attributes the fiscal results of municipal management to mayors. However, taking into consideration the Human Capital Theory, we sought to verify the influence of the legislative municipal power on this issue. The sample was comprised of Brazilian municipalities from 2013 to 2019. The quantitative descriptive methodology with longitudinal section and multiple linear regression was used to analyze the phenomena discussed in this research. The fiscal performance was measured based on the Fiscal Autonomy Index (IAF), general IFGF, IFGF autonomy, IFGF personnel, IFGF liquidity and IFGF investment. In order to measure the Human Capital, the following information was considered: one’s education level, age and occupation in public administration before inauguration. The results showed that mayors’ and councilors’ Human Capital has influence on fiscal performance in general terms.